2010
DOI: 10.1038/ajg.2010.48
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rotating Shift Work on the Prevalence of Irritable Bowel Syndrome in Nurses

Abstract: OBJECTIVES-Shift work has been associated with gastrointestinal symptoms such as abdominal pain, constipation, and diarrhea. These symptoms overlap with those reported by patients with functional bowel disorders. Because shift work will lead to misalignment between the endogenous circadian timing system and the external 24 h environment, we hypothesized that nurses participating in shift work will have a higher prevalence of functional bowel disorders when compared with nurses participating in day shifts.METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
163
4
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(183 citation statements)
references
References 22 publications
(22 reference statements)
9
163
4
7
Order By: Relevance
“…Such findings are further supported by studies with nurses and medical residents who report more GI symptoms when working shift work or nights (Nojkov, Rubenstein, Chey, & Hoogerwerf, 2010).…”
Section: Sleepsupporting
confidence: 65%
“…Such findings are further supported by studies with nurses and medical residents who report more GI symptoms when working shift work or nights (Nojkov, Rubenstein, Chey, & Hoogerwerf, 2010).…”
Section: Sleepsupporting
confidence: 65%
“…This is similar to the finding of Nojkov et al [24] among rotating shift nurses. The similarity of this finding may support the role of circadian rhythm in the pathogenesis of IBS in shift workers.…”
Section: Discussionsupporting
confidence: 82%
“…Association between the ranks of the subjects and the occurrence of IBS showed that 11 (21.2%) each are NOs practice had the highest risk of developing IBS. This is in contrast to the finding of Nojkov et al [24] where no association was found between the number of years of practice and IBS. Possible explanation for this may be because, as the number of years of practice increased the colon could adapt to changes in environmental conditions without compromising its motility.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…It has been reported that shift work is associated with cancer, diabetes, gastrointestinal disorders, metabolic and cardiovascular disease (Knutsson, 2003;Kubo et al, 2006;Lie, Roessink, & Kjaerheim, 2006;Mosendane, Mosendane, & Raal, 2008;Nojkov, Rubenstein, Chey, & Hoogerwerf, 2010;Pan, Schernhammer, Sun, & Hu, 2011;Wang, Armstrong, Cairns, Key, & Travis, 2011), and the proposed underlying mecha-nisms encompass circadian rhythm disruption, light at night, sleep deprivation, immune depression, lifestyle changes and stress (Boivin & Boudreau, 2014;Brondel, Romer, Nougues, Touyarou, & Davenne, 2010;Bushnell, Colombi, Caruso, & Tak, 2010;Crispim et al, 2011;Fritschi et al, 2011;Hansen, 2001). Specifically, in relation to healthcare work, in which non-regular and night work hours are commonly seen, there is evidence, most of it from studies in nurses, about how this type of job organization can affect workers in a negative way, both physiologically and psychologically (Admi, Tzischinsky, Epstein, Herer, & Lavie, 2008).…”
Section: Introductionmentioning
confidence: 99%